Proposing a tool for assessing sustainable practices in the work sites and measuring it in construction projects in Syria - حواط سلمى; رنا ميا; جمال عمران (Latakia University Journal -Engineering Sciences Series, 2023)
The construction industry has been criticized as an unsustainable industry due to its low productivity and high consumption of resources, as well as the fact that the construction sector accounts for the largest percentage of negative impacts on the surrounding environment. Researchers have proposed many sustainability assessment systems in the past decade but there has not yet been an effective tool to evaluate and achieve sustainability at the project level expected from the perspective of stakeholders and furthermore the absence of consideration of the application of sustainable practices on construction sites from the beginning of the project. This research aims to Proposing a tool for assessing sustainable practices in the work sites and measuring it in construction projects in Syria. The process was carried out by proposing a model for evaluating sustainable practices on the construction site in the form of a checklist within a spreadsheet and completed through field visits to the work site and personal interviews. The necessary criteria for the proposed model were developed based on previous studies, which were divided into three environmental, social and economic project management categories that include main criteria: energy, water, pollution, sustainable location, materials and waste, security, occupational health and safety, indoor environmental quality, and protection of cultural heritage. , local economy and project management, and each main standard has many sub-criteria. The measurement tool was applied to 6 different construction projects in Syria. It was found in this study that the sustainable practices that are applied on construction sites for construction projects in Syria are very weak.